2008
DOI: 10.1111/j.1365-2125.2008.03159.x
|View full text |Cite
|
Sign up to set email alerts
|

Candidate mechanisms for capecitabine‐related hand–foot syndrome

Abstract: WHAT IS ALREADY KNOWN ABOUT THIS SUBJECT• Hand-foot syndrome (HFS) is a limiting toxicity of the widely used fluorouracil (5FU) prodrug capecitabine.• The pharmacological origin of HFS has not been elucidated.• The expression of capecitabine-metabolizing enzymes thymidine phosphorylase (TP, activating pathway) and dihydropyrimidine dehydrogenase (DPD, catabolic pathway) in the skin of the palm (target tissue for HFS) is unknown. WHAT THIS STUDY ADDS• This pilot study, conducted in healthy volunteers, clearly d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
104
0
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(108 citation statements)
references
References 28 publications
0
104
0
4
Order By: Relevance
“…This could also take place in normal tissues. In particular, cell cytotoxicity could be accentuated by the elevated proliferation rate observed in the skin of the palm and sole, rendering them more sensitive to the cytotoxic effects of the 5-FU (21). This model may explain the capecitabine-related HFS variability found in treated patients.…”
Section: Discussionmentioning
confidence: 84%
“…This could also take place in normal tissues. In particular, cell cytotoxicity could be accentuated by the elevated proliferation rate observed in the skin of the palm and sole, rendering them more sensitive to the cytotoxic effects of the 5-FU (21). This model may explain the capecitabine-related HFS variability found in treated patients.…”
Section: Discussionmentioning
confidence: 84%
“…Regarding interindividual differences in HFS susceptibility, it is likely that differences in activities of CDA, TP and DYPD 4,19,20) or inducibility of cyclooxygenase 2 21) in the palmar and plantar tissues might be responsible. A recent study identified a single nucleotide polymorphism (SNP) in the promoter region of the CDA gene that is related to capecitabine-induced HFS.…”
Section: Discussionmentioning
confidence: 99%
“…One possible reason is the difference of DPD activity between skin sites. Expression of DPD metabolizing 5-FU is significantly greater in the palm than the back 22) . Further research is required regarding the difference between ethnic groups and mechanism of HFS.…”
Section: Discussionmentioning
confidence: 93%